Comparative approach for the isolation of genes involved in the osmotolerance of wheat - Zhiponova, Mira; Szilák, László; Erdei, László; Györgyey, János; Dudits, Dénes (Acta Biologica Szegediensis, 2002)
Improving drought tolerance of wheat is of great agronomical importance. Gene isolation techniques based on expression properties may provide new tools for breeders both in early characterization of new cultivars and in improving drought tolerance via molecular breeding. The main aim of our project is to isolate new drought activated genes which may serve both purposes. As a first step, a subtracted cDNA library was prepared, which represents the difference in the mRNA populations of wheat plantlets grown under 400 mOsm polyethylene-glycol derived osmotic stress versus plantlets grown in optimal conditions. By applying the subtraction approach, the resulted cDNA library becomes enriched in clones of differentially expressed genes including the ones of rare messages as well. This allows us to clone these genes, sequence them and, later, perform in silico analysis. Our first results indicate that the resulted library is enriched in clones coding for membrane associated channel proteins as well as abscisic acid and stress responsive ones.